KH. MUHAJIRIN AMSAR CONTRIBUTION ON LEGAL HADITH INTERPRETATION - Masykur Hakim (Program Studi Ilmu Agama Islam Program Magister, Universitas Islam Indonesia, 2016)
Subul al-Salam and Misbah al-Dhalam show that both lecturers have similarities and differences in explanation. The similarities of the both scholars devide into eight points of opinion concerning with the hadith related to the matter of sleep and wudhu’. The difference is that Al-Shana'niy explained the hadithin terms of grammar before explaining its contain, then he provides his own opinion after the other earlier scholars opinion. While KH Muhajirin Amsar explained hadith by ignoring other scholars opinion in terms of grammar, so that the reader can immediately understand the content of the hadith. He also did not provide his own opinion after the scholar’s opinion, it seems he more likely put the reader to choose freely due to the problem as the issue of khilafiyyah. Each has its own added value and has made a significant contribution in the context of hadith legal description that contained in the book of Bulughal-Maram including KH Muhajirin Amsar, The native Betawi scholars.